Charlie Gard and the Limits of Parental Authority - Caplan, Arthur (The Hastings Center report, 2017)
The parents of Charlie Gard, who was born August 4, 2016, with an exceedingly rare and incurable disease called mitochondrial DNA depletion syndrome, fought a prolonged and heated legal battle to allow him access to experimental treatment that they hoped would prolong his life and to prevent his doctors from withdrawing life-sustaining care. Charlie's clinicians at the Great Ormond Street Hospital in London believed that the brain damage Charlie had suffered as a result of frequent epileptic seizures, along with many other severe disabilities, would render any innovative therapy futile, and they disagreed with his parents’ wishes to use an experimental therapy. They felt it in Charlie's best interest that he be allowed to die. A battle ensued among Charlie's parents, his doctors, and a guardian who had been appointed to represent him that drew the attention of politicians and prominent persons from all over the world. The case was much in the news over the past year, but it has also been frequently misunderstood.